2023
DOI: 10.1371/journal.pone.0280471
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation is linked to classical risk factors of Alzheimer’s disease-related dementias

Abstract: Alzheimer’s disease and related dementias is a major public health burden–compounding over upcoming years due to longevity. Recently, clinical evidence hinted at the experience of social isolation in expediting dementia onset. In 502,506 UK Biobank participants and 30,097 participants from the Canadian Longitudinal Study of Aging, we revisited traditional risk factors for developing dementia in the context of loneliness and lacking social support. Across these measures of subjective and objective social depriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Recent work by Shafighi et al (26) found cross-sectional associations between social isolation and common risk factors of Alzheimer's disease and related dementias, including physical activity. Our work builds on these findings by examining the relationships between social isolation, physical activity (an Alzheimer's disease and related dementia risk factor), and cognitive decline over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Shafighi et al (26) found cross-sectional associations between social isolation and common risk factors of Alzheimer's disease and related dementias, including physical activity. Our work builds on these findings by examining the relationships between social isolation, physical activity (an Alzheimer's disease and related dementia risk factor), and cognitive decline over time.…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation is associated with poor cognitive function and greater dementia risk in later life (21)(22)(23)(24). Furthermore, greater social isolation among older adults is associated with reduced physical activity and increased sedentary time (25,26). Social isolation may reduce social activities and inherent activity level, and may deprive individuals of encouragement from friends and families to be active (25).…”
Section: Introductionmentioning
confidence: 99%
“…PLS-C is particularly useful when trying to identify patterns in very large and strongly correlated data, such as in clinical populations where patients often report symptom domains or diseases that overlap. 42,43 In our previous work, PLS-C was used to study how loneliness manifests itself in the brain's anatomy 42 and, separately, how clinical risk factors for social isolation predispose people to dementias. 43 In our study, PLS-C was thus used to identify the most explanatory projections that yielded maximal covariance between sets of brain volumes in the context of participant reports of pain experience, aiming to yield neurobiologically-grounded profiles of pain experience.…”
Section: Methodsmentioning
confidence: 99%

Pain Can’t Be Carved at the Joints

BARRON,
Saltoun,
Kiesow
et al. 2023
Preprint
Self Cite
“…Loneliness and social isolation are widespread and significant public health risks affecting many people and placing them at enhanced risk for AD. In an analysis of 502,506 British Biobank participants and 30,097 Canadian Longitudinal Study of Aging participants, Shafighi et al evaluated risk factors for developing AD in the context of loneliness and aberrant social networking support; they identified strong links between social isolation and AD [156]. Similarly, in a study to establish Cox proportional hazard models with social isolation and loneliness as separate exposures, Shen et al concluded that social isolation is a risk factor for AD that is independent of loneliness [157].…”
Section: Social Isolationmentioning
confidence: 99%